Idealized past, exclusivist present: right-wing appropriation of the decolonial rhetoric in Malaysia - Hew, Wai Weng (Critical Asian studies, 2024)
Scholars have often assumed that a decolonial agenda would empower emancipatory and anti-racist movements. Nevertheless, there is also increasing recognition by scholars that the language of decolonization has been co-opted to support right-wing ideologies and majoritarian agendas, most prominently in India and Turkey. Similarly, in Malaysia, right-wing actors use decolonial rhetoric to criticize ethnic, religious, gender, and sexual minorities and silence their demands for equal rights. These actors have justified their intolerance by labelling any perceived threats to heteronormative Malay Muslim identity as examples of “Western imperialism” or “Chinese colonialism.” This article illustrates how decolonial vocabulary has been transformed into Sinophobia and homophobia by a right-wing Islamist group in Malaysia. It shows how revisionist nativist historiography, racism, and conspiracy theories can be integrated with moralistic calls for decolonization. Tracing developments over the past decade, the paper demonstrates how persistent dissemination, intellectual laundering, and innovative marketing strategies have helped mainstream a nativist Islamist decolonial agenda in Malaysia. (Crit Asian Stud/GIGA)